Comparing Students of Medical and Social Sciences in Terms of Self-Assessment of Perceived Stress, Quality of Life, and Personal Characteristics - Wielewska, Magda K.; Godzwon, Julia M.; Gargul, Kacper; Nawrocka, Emma; Konopka, Kinga; Sobczak, Krzysztof; Rudnik, Agata; Zdun-Ryzewska, Agata (Frontiers in Psychology, 2022)
The aim of this study was to compare medical and social sciences students’ outcomes in terms of self-perceived stress, quality of life, and personality traits. We put particular emphasis on external and internal differences in students of specific fields - medicine, nursing, psychology, and pedagogy. 1783 students from the Medical University of Gdansk and the University of Gdansk participated in our study, of whom 1223 were included in the final statistical analysis. All of them were evaluated using valid and reliable questionnaires - TIPI-PL, PSS-10, and a one-item scale of quality of life. Stress turned out to have a negative effect on the quality of life, regardless of the type of field of study. Moreover, students from different fields varied in terms of personality factors: conscientiousness, agreeableness, openness to experience, and emotional stability. In conclusion, many students regardless of their field suffer from high stress and report low quality of life, which potentially further affects their academic performance and social life.